Tight Gas Completions Conference 2010
DOI: 10.2118/137996-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improving Well Completion via Real-Time Microseismic Monitoring: A West Texas Case Study

Abstract: This paper presents a case history of hydraulic fracture stimulation treatments performed on a vertical well completion in the Spraberry-Wolfcamp formations located in Midland County, Texas, in which real-time microseismic Hydraulic Fracture Monitoring (HFM) was utilized to "track" the development of the hydraulic fracture as it propagates through the formation thereby allowing for the implementation of corrective actions to improve the completion efficiency of the well.The case history is presented in three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In North America the technology is being deployed in both conventional and unconventional resources plays. 25 shows map view of the microseismic events, fracture orientation determined from the microseismic events and the derived fracture orientation from the processed dipole sonic, there is a close match between the two (Ejofodomi et al 2010). 24 is a visual representation of fracture length interpreted from microseismic results .…”
Section: Microseismic Hydraulic Fracture Monitoring Application To Rementioning
confidence: 80%
See 1 more Smart Citation
“…In North America the technology is being deployed in both conventional and unconventional resources plays. 25 shows map view of the microseismic events, fracture orientation determined from the microseismic events and the derived fracture orientation from the processed dipole sonic, there is a close match between the two (Ejofodomi et al 2010). 24 is a visual representation of fracture length interpreted from microseismic results .…”
Section: Microseismic Hydraulic Fracture Monitoring Application To Rementioning
confidence: 80%
“…In recent years, microseismic monitoring of the hydraulic fracturing treatment has become widely accepted as a critical diagnostic technology to image, quantify and evaluate the fracture geometry (orientation, length, and height) dynamics and to optimize the stimulation treatment in different ways (Warpinski et al 1998;Wolhart et al 2006;Daniel et al 2007;Le Calvez et al 2007;Warpinski et al 2009;Downie et al 2010;Ejofodomi et al 2010;Cipolla et al 2011). In North America the technology is being deployed in both conventional and unconventional resources plays.…”
Section: Microseismic Hydraulic Fracture Monitoring Application To Rementioning
confidence: 99%
“…It can be seen that if the excess stresses or horizontal strains can be obtained, then the horizontal stresses in the isotropic rock can be calculated from Eqs. ( 7) and (9). It has been found that if the measured excess stresses are available (e.g., [16]), Eq.…”
Section: Calculations Of the Horizontal Stresses From The Tectonicmentioning
confidence: 99%
“…By integrating this method to drilling-induced tensile fractures and wellbore breakouts shown in Figure 9, the maximum horizontal stress 31) for three maximum horizontal strains (dash lines). 9 Geofluids can be obtained. If σ h = 73 MPa and ε H = 1000 microstrains, then the maximum horizontal stress from Figure 10 is σ H = 98:2 MPa.…”
Section: Maximum Horizontal Stress Estimation Frommentioning
confidence: 99%
“…The authors discuss how microseismic monitoring was introduced as a new technology in the Wolfberry formation to help understand fracture behavior during stimulation treatments. Real-time micro-seismic monitoring helped "identify undesired fracture growth," and as a result, the "perforation scheme and treatment design" was changed, resulting in improved treatment and "operational efficiency" (Ejofodomi et al 2010).…”
Section: Business Problemmentioning
confidence: 99%